2021
DOI: 10.1515/bejeap-2020-0253
|View full text |Cite
|
Sign up to set email alerts
|

The Intended and Unintended Effects of Opioid Policies on Prescription Opioids and Crime

Abstract: In response to the opioid crisis, US states have implemented policies to reduce the dispensing of opioids and curb drug mortality. Exploiting a long panel of county-level data, we analyse the combination of demand- and supply-side state opioid policies and evaluate their effect on opioids per capita dispensed and their unintended fallouts on drug-related crime. We demonstrate that only laws targeting the supply for opioids reduce the volume of prescribed drugs, while demand-side policies are less effective. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Some reports in the literature have indicated positive effects of these programs in decreasing rates of opioid prescriptions overall 24,25 and specifically in pediatric orthopaedics 26,27 , reducing overdoses 28 , and decreasing prescriptions for unnecessarily high doses 29 . However, others have reported mixed results and poor implementation [30][31][32][33] . Our investigation showed that non-opioid analgesia was effective following CRPP for pediatric supracondylar humeral fractures; thus, electronic prescribing pathways and standardized institutional protocols could be updated such that oxycodone prescriptions are not automatically prompted for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports in the literature have indicated positive effects of these programs in decreasing rates of opioid prescriptions overall 24,25 and specifically in pediatric orthopaedics 26,27 , reducing overdoses 28 , and decreasing prescriptions for unnecessarily high doses 29 . However, others have reported mixed results and poor implementation [30][31][32][33] . Our investigation showed that non-opioid analgesia was effective following CRPP for pediatric supracondylar humeral fractures; thus, electronic prescribing pathways and standardized institutional protocols could be updated such that oxycodone prescriptions are not automatically prompted for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly cited reasons for the switch to heroin were (1) heroin became more accessible and significantly cheaper, (2) it was easier to inhale or inject, and (3) its potency was much greater than that of prescription opioids (Cicero et al., 2014; Mars et al., 2014; Unick et al., 2014). Deiana and Giua (2021) find that regulations restricting the supply of prescription opioids were accompanied by negative externalities in the local market for illicit drugs, measured by opium possession and sales arrests.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…Note that the Google trends analysis by itself suggests one of two possibilities: (1) restrictions in the supply of prescription opioids led users to seek out substitutes in the open marketplace or (2) the resulting increase in heroin deaths led to an increase in public interest in the phenomenon. However, given the additional finding that consumption of illicit street drugs increased following the PDMP mandates (Deiana & Giua, 2021), the first mechanism seems more plausible. Future research is needed to further pinpoint the causal pathway.…”
mentioning
confidence: 99%